2019
DOI: 10.24349/acarologia/20194333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the essential oil from the latex of the fruit Mangifera indica L. on Tetranychus urticae Koch (Acari, Tetranychidae)

Abstract: Tetranychus urticae Koch is a cosmopolitan pest that causes damage to crops in protected farming activities in the semiarid region of the state of Pernambuco, Brazil. We investigated the lethal and sublethal effects of the essential oil from the latex of the mango fruit [Mangifera indica, Espada and Rosa (MESPA and MROSA) varieties] and selected monoterpenes on T. urticae. The yield of the MROSA oil was higher (9.22 ± 0.15%). The GC/MS analysis of the oils enabled the identification of 26 constituents. Terpino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…However, the multiplication of yeasts and molds in the EO-free sample has been considerably evolved to respectively reach 2.39 log CFU/g 9 days of storage at 4 °C. These results confirmed the potential inhibitory effect of the active major volatile compounds as δ-Elemene, α-pinene and camphor in the studied EO towards this flora which closely depends on the quantity added (Cabarkapa et al, 2013; Carvalho et al, 2019).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, the multiplication of yeasts and molds in the EO-free sample has been considerably evolved to respectively reach 2.39 log CFU/g 9 days of storage at 4 °C. These results confirmed the potential inhibitory effect of the active major volatile compounds as δ-Elemene, α-pinene and camphor in the studied EO towards this flora which closely depends on the quantity added (Cabarkapa et al, 2013; Carvalho et al, 2019).…”
Section: Resultssupporting
confidence: 82%
“…These findings proved the bacteriostatic activity of T. articulata towards TC and FC. In this context, the results of Shaltout et al (2017) showed that thyme ( Thymus vulgaris ) and cinnamon ( Cinnamomum zeylanicum ) EOs decreased effectively TC count at the 3 rd and 6 th day of storage period in minced meat when compared to the control. In addition, higher concentration of thyme EO decreased significantly enterobacteraceae count at refrigerated temperature.…”
Section: Resultsmentioning
confidence: 94%
“…The two-spotted spider mite (TSSM) -Tetranychus urticae Koch (Acari: Tetranychidae), is a widespread mite (De Carvalho Ribeiro et al 2019) found in all climate zones. The database of its host plants includes about 1,275 species representing 70 genera and dozens of botanical families (Migeon and Dorkeld 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The two-spotted spider mite, Tetranychus urticae Koch (Acari family Tetranychidae), is a harmful pest that damages many crops, including vegetables, fruits, and ornamental plants [1]. It is also the most common plant-eater of the family Tetranychidae [2], attacking 3877 host crops of both greenhouse and field crops [1]. The two-spotted spider mite is polyphagous; it can feed on hundreds of plants, including many that are important for the economic well-being of countries.…”
Section: Introductionmentioning
confidence: 99%